The Response of Skeletal Muscle-Expressed Neurotrophins to Acute Resistance Exercise in Male Wistar Rats - Rasoul Eslami; Reza Gharakhanlou; Abdol-Hossein Parnow (The Society of Aging and Physical Activity (SAPA), 2018)
Background. BDNF and NT-4/5 have been proposed to be involved in the coordinated adaptations of the neuromuscular system to the elevated level of activity, but an activity-dependent expression of neurotrophins in skeletal muscle is not well established. Objectives. We, therefore, investigated the effect of one session of resistance exercise on mRNA expression of some neurotrophins in Slow and fast muscles of Wistar rats. Methods. The resistance training protocol consisted of climbing a 1-meter-long ladder, with a weight attached to a tail sleeve. Twenty-four hours following the main training session, Soleus and Flexor Hallucis Longus (FHL) muscles were removed. mRNA expression of BDNF, NT4/5, TrkB and p75 proteins was assessed by Quantitative RT-PCR. Results. The data analysis showed that one session of resistance exercise significantly (p<0.05) decreased mRNA expression of NT4/5 in soleus muscle, but not in FHL muscle. No significant effects of one resistance exercise bout were detected for BDNF and trkB. Our results also show that p75 mRNA levels in the soleus muscle were significantly elevated (7folds) after one resistance training bout (p<0.05). Conclusion. The results indicate differential control of BDNF and NT-4/5 expression following resistance exercise in skeletal muscle. Also, we have provided evidence supporting the role of the p75 receptor in neurotrophins response to resistance exercise as a mechanical stimulus.